Age-related sarcopenia index and functional capacity in elderly community members: a correlational study - Letieri, Rubens Vinícius (2022)
Sarcopenia affects performance in simple activities of daily life, directly impacting the quality of life of the elderly. The objective of the present study was to analyse the correlation between age, sarcopenia index and functional capacity in community-dwelling elderly. The sample comprised 40 community-dwelling elderly, 12 men (69.16± 8.13 years) and 28 women (67.96± 6.23 years). All participants underwent the Electrical Bioimpedance (BIA), Handgrip Strength test (HS), and Timed-Up-and-Go test (TUG). A strong correlation was found between age x TUG in men (r= 0.733; p= 0.021), between age x fat mass in women (r= 0.775; p= 0.032), between HS and TUG in men (r= − 0.713; p= 0.0003), and a weak correlation between HS and Free Fat Mass in women (r= 0.394; p= 0.043). Weak negative correlations were found regarding age in both men and women. In functional performance, concerning test time and age, strong correlations were found for men and weak correlations for women.